Force-Based Label Placement for Dynamic Data - Ekman, Sebastian (My University, 2018)
In this thesis a new method for placing graphical labels on moving objects in realtime maps is presented. The intended use case is command and control systems, such as software used by emergency response dispatchers. The method expands on previous work on force-based labeling. To ensure that the readability of labels is high and sudden movements are limited, new force components are included. Most notable of these are forces that act on labels in the direction of travel for another label, in such manner that space is made for it. The method presented is then tested on several relevant data sets that could make up future use cases and some simulated data sets. The tests are used to determine possible parameter values to be used, something that is shown to be dependent on the type of data and personal preferences. Also, the tests show that the method preforms sufficiently fast to be used in real-time applications. A video demonstration can be found on https://youtu.be/GiUzVvo0f1s.
Keywords: Data- och informationsvetenskap; Computer and Information Science